2006
DOI: 10.1161/circulationaha.105.001537
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Coronary Revascularization

Abstract: Integrated revascularization treatment plans provide minimally invasive options for patients with multivessel coronary artery disease. This approach may be accomplished with no mortality, low perioperative morbidity, and excellent angiographic LIMA patency. The reintervention rate after PCI in this series was higher than that reported elsewhere and should be investigated further. The choice of suitable vessel, type of stent and timing of the treatment must be carefully considered before implementing this hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 20 publications
1
73
0
3
Order By: Relevance
“…An international multicenter trial reported the feasibility of robotically assisted TECAB with no mortalities or strokes. 38 In this study, early patency rates of robotically sutured left IMA grafts were encouraging, at 96.3%. Our group performed the first simultaneous robotic hybrid coronary interventions in which both TECAB and percutaneous coronary intervention were performed in a single session.…”
Section: Robotic Coronary Artery Bypass Grafting As Part Of Hybrid Comentioning
confidence: 54%
“…An international multicenter trial reported the feasibility of robotically assisted TECAB with no mortalities or strokes. 38 In this study, early patency rates of robotically sutured left IMA grafts were encouraging, at 96.3%. Our group performed the first simultaneous robotic hybrid coronary interventions in which both TECAB and percutaneous coronary intervention were performed in a single session.…”
Section: Robotic Coronary Artery Bypass Grafting As Part Of Hybrid Comentioning
confidence: 54%
“…26 -40,42-51 Being a strong reflection of operator experience, results from single-center series can vary considerably. Katz et al 36 acknowledged that although they achieved excellent perioperative results from a robotically mediated endoscopic approach in 27 patients, their reintervention rate exceeded that reported elsewhere. The exceptionally high restenotic rate of 26% (3 bare metal stents and 4 DES) likely reflects lesion complexity and operator experience and therefore must be interpreted with caution.…”
Section: Hcr: What Is the Evidence?mentioning
confidence: 91%
“…Several groups have reported on successful application of TECAB in hybrid procedures since the mid 2000s [9,[14][15][16][17][18][19][20][21]. These papers clearly demonstrate that the robotic technique is reproducible.…”
Section: Minimally Invasive Surgical Approachesmentioning
confidence: 99%
“…As drug eluting stents were developed they were immediately used in hybrid coronary interventions [8,15,16,18,19] because improved short-and long-term results of the PCI part of the concept were expected. Drug eluting stents are currently used in the vast majority of hybrid coronary interventions [8,[23][24][25].…”
Section: Catheter-based Interventions In Hybrid Proceduresmentioning
confidence: 99%